Antiviral activity of withanolide a against diferent infectivity phases of dengue virus serotype 2 in Vero cell line - Lujin Al Quwatli; Michelle felicia lee; Yuan, Seng Wu; Chit, Laa Poh; Kalaivani Batumalaie; Nafees Ahemad; Neeraj Kumar Fuloria; Shivkanya Fuloria; Mahendran Sekar; Vetriselvan Subramaniyan; Moklesur Rahman Sarke; Rhanye Mac Guad (Springer Nature, 2024)
Dengue fever is caused by the Aedes mosquito-borne dengue virus, which is a global threat with 400 million cases reported annually and 5–20% mortality rate. Currently, there is no effective treatment available for dengue fever. Natural products like withanolides, which are steroidal lactones, have shown many good properties, including antiviral activity against other viruses. This study aimed to evaluate the anti-dengue virus serotype 2 activity of withanolide A and withanone in Vero cells. Withanolide A and withanone were well-tolerated in Vero cells with a half-maximal cytotoxic concentration of 0.4982 and 1.186 µM, respectively. Withanolide A and withanone exhibited good direct virus-inactivating effects against dengue virus serotype 2 with a half-maximal inhibitory concentration of 0.017 and 0.353 µM, respectively. Based on the selectivity index, withanolide A (selectivity index, 29.31) was determined to be safer and more effective in inhibiting dengue virus serotype 2 infection in Vero cells than withanone (selectivity index, 3.36). Further investigations conducted with withanolide A showed that it inhibited dengue virus serotype 2 during the pre- and post-infection stages in a dose-dependent manner. Withanolide A also effectively blocked dengue virus serotype 2 attachment and entry into Vero cells in a dose-dependent manner. These findings suggest that withanolide A showed potent anti-dengue activity and could serve as a promising antiviral agent for treatment of dengue infections.